2022
DOI: 10.3389/fpsyt.2022.934837
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of mental health care during the transition from prison to the community following brief periods of imprisonment

Abstract: PurposeThe prison-to-community transition period is one of high risk and need, particularly for those with mental illness. Some individuals cycle in and out of prison for short periods with little opportunity for mental health stabilization or service planning either in prison or the community. This study describes the socio-demographic, clinical and criminal justice characteristics of individuals with mental illness and frequent, brief periods of imprisonment, examines continuity of mental health care between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Our findings align with a previous NSW study among prisoners which demonstrated mental health service engagement rates of 85.5% during supervision. However, only 14.2% engaged with community-based mental health services postrelease 23…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with a previous NSW study among prisoners which demonstrated mental health service engagement rates of 85.5% during supervision. However, only 14.2% engaged with community-based mental health services postrelease 23…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative to consider not only the legal dimensions, as expounded upon here, but also the medical implications ( 59 , 67 ). The scarcity of studies exploring disorder-specific pharmacological interventions within the prison environment can be attributed to methodological complexities, such as monitoring follow-up and selecting appropriate outcome measures ( 46 , 53 ). In view of the fact that penal authorities need to offer even better health services than those available to the general population to reach comparable health outcomes ( 14 , 66 ), we advocate the investigation of ketamine treatment for PLP dealing with depression and suicidal ideation under controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that PLP are insufficiently represented in health research complicates data-driven decision-making ( 3 , 45 ). Studies in prisons are often hampered by discontinuity of care and tight financial constraints ( 53 , 54 ), which limits longitudinal research on the effectiveness of clinical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…We stratified temporal relationship to incarceration because there are different health risks associated with each. As an example, transition into and out of correctional facilities is disruptive and traumatic and can have differential effects on health [ 22 ]. Additionally, there are likely different health system level interventions that are feasible to improve care for currently and formerly incarcerated individuals due to the role of departments of corrections in managing health care.…”
Section: Methodsmentioning
confidence: 99%